The study of offspring and mothers with gestational diabetes treated with metformin or glibenclamide in a randomized controlled trial after 9 years - Praveen George Paul; Beena Ruth Kingsbury; Hilda Yenuberi; Richa Sasmita Tirkey; Santosh Joseph Benjamin; Swati Rathore; Babuji Manimegalai; Antonisamy Belavendra; Jiji Elizabeth Mathews (Current Medical Issues, 2023)
Introduction: Follow-up of the mothers and their offspring recruited to a randomized controlled trial comparing neonatal outcomes in women with gestational diabetes treated with metformin or glibenclamide was conducted 9 years ago. A significant decrease in neonatal hypoglycemia in the group treated with metformin was seen in the original study. Methodology: Results of clinical examination, blood sample collection, and dual-energy X-ray absorptiometry (DEXA) scan not published in a brief communication are described in this study. The nutritional status was assessed using a 3-day recall method using the Indian Food Composition Table 2017. The physical activity of offspring was assessed using the Global Physical Activity Questionnaire. Results: The overall follow-up rate of the cohort was 49% and similar in both the groups. The anthropometric details, blood tests, and DEXA in the women and their offspring were similar except that the offspring of the group on metformin had higher triglyceride values than the offspring of the women treated with glibenclamide. The average body mass index of the offspring was similar and was 18. Currently, women who were treated with glibenclamide 9 years ago had higher fasting plasma glucose levels (9.2 [7.3, 12.6]) than the metformin group (7.2 [6.1, 8.4] median [interquartile range]), P = 0.02. They also had significantly higher diastolic blood pressure readings 77.1mmHg (8.9) and 72.1mmHg (11.7) mean (SD), P = 0.035. (Information from the previously published brief communication). Conclusion: No significant adverse outcome was seen in women treated with metformin and the offspring 9 years later.